ANALISIS STRATEGI BISNIS PADA OLAHAN SUSU SEGAR “HOUSE OF MILK” - Witantri Kusrini; Aditya Kurnia Indrajaya; Tiara Puspa; Stevan Goklas Simanjuntak (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2022)
This study aims to determine a business strategy for SMEs in the fresh milk business in Solo with the name House of Milk. The business strategy includes a detailed analysis of Strength, Weakness, Opportunity, Threat (SWOT). After analyzing the SWOT, the next analysis was carried out using the IFE (Internal Factor Evaluation) and EFE (External Factor Evaluation) methods. Then the last step is to use the SWOT matrix. The purpose of this research is as a decision-making material on the business strategy of fresh milk SMEs in the future.